(untitled) (Archives of Mechanics - Test, 2009)
Professor Wojciech Nowacki, member of the Editorial Committee of Archives of Mechanics and Head of the Institute of Fundamental Technological Research of the Polish Academy of Sciences, passed away suddenly on 14th of August 2009.